Perbandingan Penegakan Aturan Lalu Lintas Antara Penerapan Tilang Manual Dan Electronic Traffic Law Enforcement (ETLE) Di Kota Padang - Dicaprio, Leonardo; Nova, Efren; Kurniawan, Iwan (Fakultas Hukum Universitas Andalas, 2024)
Enforcement of traffic rules is regulated in Law Number 22 of 2009 concerning Road Traffic and Transportation and Government Regulation No. 80 of 2012 concerning Procedures for Inspecting Motorized Vehicles on the Road and Enforcement of Traffic and Road Transportation Violations. The development of an electronic-based law enforcement system gave birth to Electronic Traffic Law Enforcement as an innovation to overcome obstacles in the application of manual fines. However, in its application, ETLE was also not free from various problems, so the urgency was born to conduct research to find out and compare the procedures for applying manual and ETLE tickets and how to apply future tickets in Indonesia, especially in the city of Padang as a research location. This study uses empirical juridical methods, the data used is primary data from interviews with Padang Police TMC operators and secondary data is in the form of document studies. The result of the research is that manual poles are directly imposed on violators by officers. Meanwhile, ETLE is a modern ticket system used by the police to monitor and prosecute traffic violations electronically with camera and sensor technology to identify vehicles that violate traffic rules, such as violating a red light or crossing the speed limit. Obstacles that occur in manual ticketing are low legal awareness from both law enforcers and the public. The obstacles that occur in ETLE are the limitations of static and mobile camera devices so that the application is not comprehensive. The application of fines in the future will still use a combination of manual and electronic ticketing due to the low level of public legal awareness and the uneven distribution of electronic ticketing devices in the city of Padang.